Perancangan Model Human-Centered Storytelling sebagai Panduan Strategis untuk Memperkuat Positioning Brand Popolo Coffee di Instagram - Athifa Yasmina Humaira; Abung Supama Wijaya (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This study aims to analyze the digital communication practices of Popolo Coffee on Instagram and to design a human-centered storytelling model as a strategic framework for strengthening brand positioning on social media.. A qualitative approach with a descriptive-analytical method was employed in this study. Data were collected through observation of Popolo Coffee's Instagram content, semi-structured interviews with the owner, marketing communication, and barista, as well as digital documentation consisting of content archives and post screenshots. The findings reveal that Popolo Coffee has implemented a human-centered storytelling approach through daily life content, barista activities, and customer interactions presented in a natural and organic manner; however, content management has been conducted intuitively without a formally documented strategic guideline. Analysis using the AIDA model indicates that Popolo Coffee's content is effective at the attention and interest stages, but remains suboptimal at the desire and action stages.